Need Analysis of Developing Digital Teaching Materials Based on MOOCs for Postgraduate Students - Kusen, Kusen (Graduate Program Magister Manajemen Pendidikan, 2022)
This study aims to determine the needs of IAIN Curup postgraduate students for digital teaching materials based on MOOCs. The research sample was 105 postgraduate students from 4 study programs, namely Islamic Education Guidance and Counseling, Islamic Family Law, Islamic Education Management, and Islamic Religious Education. The research instrument used is a student needs questionnaire IAIN Curup postgraduate towards digital teaching materials based on MOOCs. The data analysis technique used is descriptive statistical analysis. The results of this study are digital teaching materials based on MOOCs are urgently needed by postgraduate students of IAIN Curup. This is evidenced by the percentage gain from the results of filling out the needs analysis questionnaire for digital teaching materials based on MOOCs, which is 87.5%, which means that students strongly agree to the development. These results will have an impact on the use of technology in the development of teaching materials.